The legal regulation of investment activity in the field of the protection and use of mineral resources (Journal of actual problems of jurisprudence, 2018)
This article discusses the issues of legal regulation of investment activity in the field of protection and use of mineral resources. The problems of the introduction or improvement of the investment, environmental, land and legislation of subsoil usage, national legislation granting the right to use subsoil.Questions investment agreement in the field of mineral resources.Suggestions for optimizing the decision-making process for the protection and realization of investments.Key words: legal regulation, subsoil, environmental protection, investment.